Bonnard - Whitfield, Sarah, 1942-; Elderfield, John; Tate Gallery. Trustees; Museum of Modern Art (New York, N.Y.) (New York, N.Y. : Harry N. Abrams, 1998)
"Pierre Bonnard (1867-1947) is among the most enigmatic of the great masters of twentieth-century painting. In this book, Sarah Whitfield and John Elderfield bring a new understanding to his deeply serious, complex paintings." "Published to accompany a major retrospective exhibition at the Tate Gallery, London, and at The Museum of Modern Art, New York, Bonnard features two important essays based on much fresh research. Sarah Whitfield, curator of the exhibition, discusses the legacy of the Symbolism of Bonnard's early years and the way in which his acceptance of nature's surrender to time finds expression in the grand elegiac paintings of the later period. John Elderfield, curator of the exhibition at The Museum of Modern Art, writes about Bonnard's awareness of the complexities of visual perception, and how crucial an understanding of this is to fully comprehending his stature as a painter."--Jacket.
Published to accompany the exhibition ... held at the Tate Gallery, 12 February-17 May 1998 and at the Museum of Modern Art, 17 June-13 October 1998.
Includes bibliographical references (pages 264-265) and index.
Keywords: Bonnard, Pierre, -- 1867-1947 -- Criticism and interpretation